Nowe kino saudyjskie. O twórczości Meshala Al Jasera - Linek, Ewa (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2024)
The author analyzes two films by the young Saudi director Meshal Al Jaser: Is Sumiyati Going to Hell? (2016) and Can I Go Out? (2017), in which she focuses on the situation of two social groups – women and migrant workers. The analysis is preceded by a short introduction to the social and cultural situation in Saudi Arabia, together with a description of the conditions that have only recently enabled the emergence of filmmaking in this country and shaped its specificity. The author focuses on the content of the films analyzed, interpreting them in the context of Saudi reality, as well as on the director’s characteristic style, which often employs the convention of grotesque. This text tries to show how the artistic choices made by Al Jaser allow him to portray the chosen social phenomena in their depth and complexity.